Ask a question
0 0


I don't understand what to do with the first part of the problem.
Tutors, please sign in to answer this question.

2 Answers

 Basically this is equation to solve for m
 1/ 3 m + 2/3 m = -1
   3/3 m = -1
     m = -1/ 1 = 1
I think you want to solve for m. If you multiply both sides of the equation by m you will have
1/3+2/3=-m so m=-1 because 1/3+2/3 =1 Does this help?


While you arrived at the correct answer, saying "multiply both sides of the equation by m" is actually misstated because "1/3m" is not "1 / 3m" it is actually "1m / 3" or "m/3"
Thus the equation would actually read,
m/3 + 2m/3 = -1
The denominator for both fractions is 3, thus the equation becomes,
3m/3 = -1
Same answer, just the equation and method for solution worded more accurately.